Предмет: Алгебра,
автор: zcat2010
решить данное уравнение
(x-4)(x-2)(x-1)(x+1)=112
Ответы
Автор ответа:
0
((x-4)(x+1)) * ((x-2)(x-1)) = 112
(x^2 - 3x - 4) * (x^2 - 3x + 2) = 112
x^2 - 3x - 1 = t:
(t - 3)(t + 3) = 112
t^2 - 9 = 112
t^2 = 121
t = +-11
а) t = 11
x^2 - 3x - 1 = 11
x^2 - 3x - 12 = 0
D = 9 + 4*12 = 57
x = (3 +- sqrt(57))/2
б) t = -11
x^2 - 3x - 1 = -11
x^2 - 3x + 10 = 0
D = 9 - 40 <0
Ответ. (3 +- sqrt(57))/2
(x^2 - 3x - 4) * (x^2 - 3x + 2) = 112
x^2 - 3x - 1 = t:
(t - 3)(t + 3) = 112
t^2 - 9 = 112
t^2 = 121
t = +-11
а) t = 11
x^2 - 3x - 1 = 11
x^2 - 3x - 12 = 0
D = 9 + 4*12 = 57
x = (3 +- sqrt(57))/2
б) t = -11
x^2 - 3x - 1 = -11
x^2 - 3x + 10 = 0
D = 9 - 40 <0
Ответ. (3 +- sqrt(57))/2
Похожие вопросы
Предмет: Қазақ тiлi,
автор: adiakusmanova
Предмет: Английский язык,
автор: maksikaksyonov
Предмет: Математика,
автор: Аноним
Предмет: Обществознание,
автор: 23Ирина1
Предмет: Химия,
автор: Mirta666